The role of halal industry in activating the tourism market in the Philippines - Tagaranao, Mariam Saidona; Gamon, Alizaman Dumangcag (2017)
Halal is a global industry that provides significant contribution to the tourism market for both majority and minority Muslim countries. The halal market implications for economic development is relatively recent to the Philippine Government. Thus, there is no single and unified halal standard followed by accrediting bodies in the country towards tourism industries. For Philippines to hold a good position in the global halal tourism market, the government should have to take into consideration a number of Islamic halal requirements. This study addresses the following issues: Awareness on the Islamic principles of halal industry; Philippine tourism policies on halal industry; Philippine halal certifying bodies; and enhancement of Philippine halal tourism industry. This study will use qualitative method with content analysis approach in evaluating the Philippine tourism policies in relation to halal principles. It has been recommended that halal council should be established with expert Muslim members in the field of halal marketing. For economic sustainability, the government has to explore and discover more local and international halal tourism opportunities.